Factitive Verbs in Hungarian - Szabo, Laszlo (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1990)
The purpose of this study is a classification of the Hungarian factitive verbs on the basis of their optimal environment in the sentences: V(NNV) . While the causative verbs of Hungarian have been studied by many scholars, I am the first to investigate the "factitive" verbs. In this paper, a list of the Hungarian factitive verbs will be presented, as well as new observations about regularities in the behaviour of the four words : V/1, V/2 , N/1 and N/2. There are surprising regularities in occurrence, or the lack of occurrence, of certain combinations of grammatical forms in Hungarian sentences with factitive verbs.